Pengaruh Model Pembelajaran Cooperative Integrated Reading and Composition (CIRC) Berbasis Multimodal terhadap Peningkatan Literasi Dasar dan Berpikir Kritis Siswa Sekolah Dasar - Nazmudindireja, Mohamad Gagan; Suciati, Suciati; Nirmala, Sri Dewi (Universitas Cokroaminoto Palopo, 2025)
This research is motivated by the low levels of basic literacy and critical thinking skills in Indonesia, highlighting the need for improvement. This study aims to analyze the effect of a multimodal-based Cooperative Integrated Reading and Composition (CIRC) learning model on improving students' basic literacy and critical thinking skills. A quasi-experimental method was used, involving 30 fifth-grade students divided into two groups: 15 students at SDN Kalam Jaya (experimental group, multimodal-based CIRC) and 15 students at SDN Tunas Bakti (control group, conventional learning). Data were collected through basic literacy tests (reading and writing), critical thinking tests, questionnaires, and observations. The research instruments have been tested for validity and reliability. Data analysis used independent t-tests, paired t-tests, and descriptive analysis. The research results show that the multimodal-based CIRC model significantly improves students' basic literacy. The average post-test score in the experimental group reached 88.9, which was higher than the control group (76.8). Critical thinking skills also increased significantly, with an average post-test score of 87.6 in the experimental group compared to 76.7 in the control group. These findings are supported by questionnaires and observations that show increased learning interest, active participation, and students' ability to analyze and evaluate information. Based on these results, the multimodal-based CIRC learning model is effective in improving the basic literacy and critical thinking skills of elementary school students